(untitled) (Journal of Engineering, 2016)
The pretreatment process can be considered one of the important processes in wastewater treatment, especially coagulation process to decrease the strength of many pollutants. This paper focused on using powdered date seeds as natural coagulant in addition to chemical coagulants (alum and ferric chloride) to find the optimum dosage of each coagulant that makes efficient removal of turbidity and chemical oxygen demand (COD) from domestic wastewater as a pretreatment process, then finding the optimum combined dosages of date seeds with alum, date seeds with ferric chloride that make efficient removal for both pollutants. Concerning turbidity, the optimum dosage for date seeds, alum and ferric chloride were 40 mg/l (79%), 70 mg/l (84%) and 60 mg/l (82%) respectively. Concerning COD the optimum dosage for date seeds, alum, and ferric chloride were 40 mg/l (75%), 60 mg/l (83%) and 50 mg/l (86%). The study showed that the optimum combined dosage that made higher turbidity removal (95%) resulted from mixing 70 mg/l date seeds with 50 mg/l alum, while for higher COD removal 90% resulted from mixing 40 mg/l date sees with 70 mg/l ferric chloride.